Investigation of a monophasic Salmonella Typhimurium outbreak linked to chocolate products as part of wider international outbreak: A matched case–control study, Ireland, 2022 - Charlotte Salgaard Nielsen; Patricia Garvey; Martin Cormican; Niall DeLappe; Mary Lenahan; Orla Moore; Kay Casey; Suzanne Cotter; Sarah Gee; Benjamin Aniugbo; Gerard Meagher; Elaine Brabazon; et al. (Public Health Challenges, 2023)
Abstract Background In March 2022, an outbreak investigation was initiated in Ireland after identifying a cluster of monophasic Salmonella Typhimurium cases, affecting primarily small children. Microbiological investigations revealed that the cluster was part of a wider international outbreak. Methods A total of 18 Irish outbreak cases were identified. We undertook a matched case–control study using the case–case method to determine if exposure to the implicated products was associated with illness. Results In univariable analysis, the highest odds of disease due to monophasic S. Typhimurium versus other gastrointestinal disease were obtained for a chocolate Product A of Brand A [matched odds ratio (mOR) = 7.77, 95% confidence intervals (CI): 0.89–67.20]. When grouping the implicated products in a composite variable, the odds of disease due to monophasic S. Typhimurium versus other gastrointestinal disease were 10.5 times higher with a consumption of at least one of the implicated products [mOR = 10.50, 95% CI: 1.24–88.60, p = 0.031]. Conclusion This analytical study supported the internationally generated hypothesis which led to the implementation of control measures. Owing to the high levels of chocolate purchasing with Easter approaching, early outbreak identification and involvement in the internationally coordinated investigation was essential to an efficient response and to minimise the risk of further harm to a particularly vulnerable population group.